Structure and Properties of Barium Bismuth Titanate Prepared by Mechanochemical Synthesis - Bobic, J. D.; Stojanovic, B. D.; Paiva-Santos, C. O. [UNESP]; Zivkovic, L. J.; Vijatovic, M. M.; Cilense, M. [UNESP] (Taylor & Francis Ltd, 2008)
Bi4Ti4O15 [BBT], a member of Aurivillius bismuth-based layer-structure perovskites, was prepared from stoichiometric amounts of BaTiO3 [BT] and Bi4Ti3O12 [BIT] obtained via mechanochemical synthesis. Mechanochemical synthesis was performed in air atmosphere in a planetary ball mill. BBT ceramics were sintered at 1100C for 4 h without pre-calcination step within heating rate 10C/min. The formation of phase and crystal structure of BT, BIT and BBT were approved using X-ray analysis. The morphology of obtained powders and microstructure were exhamined using scanning electron microscopy. The electrical properties of sintered samples were carried out.
Keywords: Mechanochemical synthesis; Aurivillius phase; BaBi4Ti4O15